ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA BANK UMUM SYARIAH DI INDONESIA 2014-2018 - Yeliana Kurniawati Sunarto; Widi Hariyanti; Yunus Harjito (Universitas Palangka Raya, 2020)
This study analyzed the factors that affect the disclosure of Islamic Social Reporting by using variables of Islamic governance score, profitability proxyed by Return on Assets, firm size proxied by total assets, leverage proxied by Debt to Equity Ratio, and type bank proxied by types of sharia banks and sharia business units or sharia financing units. Islamic Social Reporting is an index of social responsibility disclosure whose indicators are specific in accordance with sharia. This research uses purposive sampling based on financial report / annual report of Syariah Commercial Bank in Indonesia during research period that is year 2014-2018. The results of this study indicate that the islamic governance score, profitability, firm size, leverage, and type bank simultaneously affect the disclosure of Islamic Social Reporting. Partially, only the firm size variables affect the disclosure of Islamic Social Reporting.